The study on the effect of voltage ripple on multiphase buck converters with phase shedding control scheme for SCADA applications - Mini P. Varghese; A. Manjunatha; T. V. Snehaprabha (Institute of Advanced Engineering and Science, 2021)
Voltage regulator modules (VRM) need to have low output voltage ripple and tight efficiency to power advanced microprocessors. This paper explains a phase shedding technique to enhance efficiency and its impact on output voltage ripple. In this study, analysis was done on a 4-phase buck converter which is having an input voltage of 45-65 V and delivers an output of 9 V, 12A with a switching frequency of 200Khz. The phase shedding control scheme is suitable for applications such as power sources for programmable logic controllers, which is a part of SCADA systems, which requires a low voltage and high current power supply. Working of a multiphase buck converter with phase shedding is modelled and verified using Matlab/Simulink software. The simulation results show the effect of the phase shedding technique on efficiency in varying load conditions and the effect of an increase of the voltage ripple at the output.